Antiplatelet drugs reduce the immunoinflammatory response in a rat model of periodontal disease - Coimbra, L. S. [UNESP]; Steffens, J. P. [UNESP]; Muscara, M. N.; Rossa, C. [UNESP]; Spolidório, Luis Carlos [UNESP] (Wiley-Blackwell, 2014)
Background and ObjectiveAfter activation, platelets express mediators that modulate inflammation. We hypothesized that drug-induced platelet inactivation may interfere in the inflammatory process in experimental periodontal disease by suppressing the release of biological mediators to the injury site.Material and MethodsTo evaluate the effects of antiplatelet drugs on experimental periodontal disease, 60 rats were randomly assigned to six groups (n=10) and ligatures were placed around lower first molars in three groups. The other three groups were not subjected to the induction of periodontal disease and were used as negative controls. During the experimental period, animals were given aspirin (30mg/kg) or clopidogrel (75mg/kg) intragastrically once daily for 3d. On day 3, they were killed and gingival tissue were used to evaluate myeloperoxidase activity and the expression of the chemokine CXCL4. Hemi-mandibles were used for microscopic evaluation.ResultsClopidogrel significantly reduced the inflammatory infiltrate and increased the amount of collagen fibers. Histometric analysis showed that clopidogrel impaired alveolar bone loss. Expression of CXCL4 was significantly increased (p<0.001) in rats subjected to periodontal disease. Systemic administration of aspirin and clopidogrel induced a significant decrease ( p<0.05) in the expression of CXCL4. Treatment with antiplatelet drugs resulted in a significant reduction of myeloperoxidase activity when compared to saline-treated animals with periodontal disease.ConclusionClopidogrel but not aspirin showed the ability of preventing bone loss in experimental periodontitis.
Keywords: inflammation; periodontal disease; polymorphonuclear leukocyte; systemic host effect